Skip to Main Content
Table 2 

Feature templates and instances for dependency parsing. Wi/Pi denotes the word/POS of the hypothetic head, Wj/Pj denotes the word/POS of the hypothetic modifier, and Px + / −1 denotes the POS to the right/left of the x-th token. Suppose we are considering the words “” (i = 2) and “” (j = 3) in “/NR-/P-/NN-/VV-/NN-/VV”.

TypeTemplatesInstances
unigram WiPi WiPi=∘NN 
Wi Wi= 
Pi Pi=NN 
WjPj WjPj=∘VV 
Wj Wj= 
Pj Pj=VV 
 
bigram WiPiWjPj WiPiWjPj=∘NN∘∘VV 
WiWjPj WiWjPj=∘VV 
PiWjPj PiWjPj=NN∘∘VV 
WiPiWj WiPiWj=∘NN∘ 
WiPiPj WiPiPj=∘NN∘VV 
WiWj WiWj= 
WiPj WiPj=∘VV 
PiWj PiWj=NN∘ 
PiPj PiPj=NN∘VV 
 
context PiPi + 1Pj − 1Pj PiPi + 1Pj − 1Pj=NN∘VV∘NN∘VV 
Pi − 1PiPj − 1Pj Pi − 1PiPj − 1Pj=P∘NN∘NN∘VV 
PiPi + 1PjPj + 1 PiPi + 1PjPj + 1=NN∘VV∘VV∘NN 
Pi − 1PiPjPj + 1 Pi − 1PiPjPj + 1=P∘NN∘VV∘NN 
Pi − 1PiPj − 1 Pi − 1PiPj − 1=P∘NN∘NN 
Pi − 1PiPj + 1 Pi − 1PiPj + 1=P∘NN∘NN 
PiPi + 1Pj − 1 PiPi + 1Pj − 1=NN∘VV∘NN 
PiPi + 1Pj + 1 PiPi + 1Pj + 1=NN∘VV∘NN 
Pi − 1Pj − 1Pj Pi − 1Pj − 1Pj=P∘NN∘VV 
Pi − 1PjPj + 1 Pi − 1PjPj + 1=P∘VV∘NN 
Pi + 1Pj − 1Pj Pi + 1Pj − 1Pj=VV∘NN∘VV 
Pi + 1PjPj + 1 Pi + 1PjPj + 1=VV∘VV∘NN 
PiPj − 1Pj PiPj − 1Pj=NN∘NN∘VV 
PiPjPj + 1 PiPjPj + 1=NN∘VV∘NN 
Pi − 1PiPj Pi − 1PiPj=P∘NN∘VV 
PiPi + 1Pj PiPi + 1Pj=NN∘VV∘VV 
TypeTemplatesInstances
unigram WiPi WiPi=∘NN 
Wi Wi= 
Pi Pi=NN 
WjPj WjPj=∘VV 
Wj Wj= 
Pj Pj=VV 
 
bigram WiPiWjPj WiPiWjPj=∘NN∘∘VV 
WiWjPj WiWjPj=∘VV 
PiWjPj PiWjPj=NN∘∘VV 
WiPiWj WiPiWj=∘NN∘ 
WiPiPj WiPiPj=∘NN∘VV 
WiWj WiWj= 
WiPj WiPj=∘VV 
PiWj PiWj=NN∘ 
PiPj PiPj=NN∘VV 
 
context PiPi + 1Pj − 1Pj PiPi + 1Pj − 1Pj=NN∘VV∘NN∘VV 
Pi − 1PiPj − 1Pj Pi − 1PiPj − 1Pj=P∘NN∘NN∘VV 
PiPi + 1PjPj + 1 PiPi + 1PjPj + 1=NN∘VV∘VV∘NN 
Pi − 1PiPjPj + 1 Pi − 1PiPjPj + 1=P∘NN∘VV∘NN 
Pi − 1PiPj − 1 Pi − 1PiPj − 1=P∘NN∘NN 
Pi − 1PiPj + 1 Pi − 1PiPj + 1=P∘NN∘NN 
PiPi + 1Pj − 1 PiPi + 1Pj − 1=NN∘VV∘NN 
PiPi + 1Pj + 1 PiPi + 1Pj + 1=NN∘VV∘NN 
Pi − 1Pj − 1Pj Pi − 1Pj − 1Pj=P∘NN∘VV 
Pi − 1PjPj + 1 Pi − 1PjPj + 1=P∘VV∘NN 
Pi + 1Pj − 1Pj Pi + 1Pj − 1Pj=VV∘NN∘VV 
Pi + 1PjPj + 1 Pi + 1PjPj + 1=VV∘VV∘NN 
PiPj − 1Pj PiPj − 1Pj=NN∘NN∘VV 
PiPjPj + 1 PiPjPj + 1=NN∘VV∘NN 
Pi − 1PiPj Pi − 1PiPj=P∘NN∘VV 
PiPi + 1Pj PiPi + 1Pj=NN∘VV∘VV 
Close Modal

or Create an Account

Close Modal
Close Modal